Anomalous Hall magnetoresistance in a ferromagnet - Yumeng Yang (Nature Portfolio, 2018)
Magnetoresistance in ferromagnetic materials and heterostructures have been enabling advanced understanding of electron transport in solids, as well as new concepts for applications. Here the authors demonstrate a different type of magnetoresistance arising from anomalous Hall effect associated spin–charge mutual conversion.